School cultures between visions and policies – findings of a document analysis of three-year educational offer plans - Seitz, Simone; Consalvo, Giulia; Dell'Anna, Silvia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
This article examines how schools articulate and communicate their pedagogical and inclusionrelated orientations through the Piano Triennale dell’Offerta Formativa (PTOF), the threeyear educational plan mandated by Italian law. Anchored in the sociology of knowledge and school culture theory, the study conceptualises PTOFs not as neutral descriptions of school reality but as social artefacts that both reflect and shape institutional knowledge discourses. The empirical basis consists of 46 PTOFs, covering all educational levels. The findings of the document analysis reveal that PTOFs serve a dual function as instruments of accountability towards external audiences and as internal reference points for school development. Their analysis offers insight into the symbolic orders, implicit norms, and discursive strategies through which school cultures navigate the interplay of autonomy, regulation, and inclusion policies.